Brand personality in careers belong to three academic areas of UNMSM - García Ampudia, Lupe (2014)
The present investigation research to study the Brand Personality in Careers belong to three Academic Areas of Universidad Nacional Mayor de San Marcos (Health, Humanities and Engineering), all them with accreditation requires. The aims were orientated to establish the features typical of brand personality of each one of the careers comparing the level of studies of the students (entry level: the first year, intermediate level: the third year, high level: the fifth year) and the genre. The population is constituted by the students’ totality registered in each of the careers and the sample by 553 students of Systems Engineering, Education and Psychology. The used instrument was the Aaker’s Brand Personality Scale, it consists of five dimensions: sincerity, competition, emotion, sophistication and hardness adapted by Denegri, M. (2009). The results establish typical different features in the careers of the sample (systems engineering, education and psychology) when it was analyzed the factors found significant differences in four factors with the exception of the factor of competition, with relation the genre, it found significant differences in seventeen features and in the levels of study it found differences in fourteen of the features of brand personality.